Association of sickle cell trait with β‐cell dysfunction and physical activity in adults living with and without HIV in Tanzania. Issue 4 (1st March 2022) - Kweka, Belinda V.; Fredrick, Cyprian; Kitilya, Brenda; Jeremiah, Kidola; Lyimo, Eric; Filteau, Suzanne; Rehman, Andrea M.; Friis, Henrik; Olsen, Mette F.; Faurholt‐Jepsen, Daniel; Krogh‐Madsen, Rikke; PrayGod, George
Abstract : This study aimed to investigate sickle cell trait (SCT) associations with physical activity, markers of insulin secretion and resistance, and glucose among people living with HIV infection (PLWH), both antiretroviral therapy (ART) naive and experienced, and HIV‐uninfected adults. This was a cross‐sectional study conducted in Mwanza, Northwestern Tanzania. We used data of 668 participants attained from two sub‐studies of CICADA study. Mean age was 40 (SD 11.5) years, 402 (61.7%) were females and 157 (24.1%) had SCT. PLWH were 422 (64.7%), of these, 80 (18.9%) were on ART. People with SCT had higher risk of having an isolated β‐cell dysfunction compared to those without SCT (RRR = 1.82, CI: 1.10, 3.01, p = 0.02). People with SCT but without HIV infection had lower average acceleration on the trunk longitudinal axis (ACCx) and higher level of self‐reported physical activity. 30 min oral glucose tolerance test among PLWH on ART was higher in those with SCT compared to those without SCT. People with SCT are at higher risk of having β‐cell dysfunction and those with SCT on ART are at more risk of developing diabetes. Future studies to investigate the interaction between SCT and HIV/ART on risk of diabetes should be considered.